Statin use as a moderator on the association between metformin and breast cancer risk in women with type 2 diabetes mellitus - Fan Zhang; Geertruida H. de Bock; Gijs W. Landman; Qingying Zhang; Grigory Sidorenkov (Cancer & Metabolism, 2024)
Abstract Introduction Metformin and statins are considered as potential agents for prevention of breast cancer, however, existing evidence does not uniformly substantiate this claim, and the data is scarce concerning their interaction in relation to breast cancer risk. This study aims to investigate whether the effect of metformin on breast cancer incidence varied by statin use among women with type 2 diabetes mellitus (T2DM). Methods This study included women with T2DM, without a history of cancers, and followed up for more than one year from the Zwolle Outpatient Diabetes project Integrating Available Care (ZODIAC) for the period 1998–2014. The dataset was structured using a person-time approach, where the cumulative medication usage was annually updated for each person. The extended Cox proportional hazards models were employed, reporting adjusted hazard ratios (HR) with 95% confidence intervals (CI). Results During a median follow-up of 5 years, 515 of 29,498 women received a breast cancer diagnosis. Each additional year of metformin or statins use corresponded to a decrease in breast cancer incidence, while the magnitude attenuated over time. Noteworthily, statin use modified the effect of metformin on breast cancer incidence. For instance, after 5 years of follow-up, one-year increase of metformin use among women who used statins for 3 years was linked to a substantially reduced breast cancer risk (HR, 95% CI: 0.88, 0.84–0.93), however, there was no significant decrease in risk for those non-statins users (HR, 95% CI: 0.96, 0.89–1.04). Conclusions Extending metformin or statin usage by one year conferred breast cancer protection in women with T2DM. Enhanced protective effect of metformin was observed among those who also use statins. These results suggest the potential of combined metformin and statin therapy as promising breast cancer prevention strategies.